War Neurosis and the Violence of Language and Form in the Terrorist Novel: A case Study of Wassini Al Araj - BADI, ABDESLAME (Milev Journal of Research and Studies, 2015)
To what extent can language symbolically reflect the violence of the black decade? How does the narrative text translate this violence from the language of reality to fictional language, and then to the language of formulation? What are the features of the structural form of violence in the narrative text of the terrorist novel ?Does psychoanalysis view this artistic violence as one of the symptoms of war neurosis? This study tries to answer the questions above by relying on a semiotic phenomenological approach to Wassini Al- Araj’s terrorist novel.